School Improvement and Academic Performance of Public Secondary Schools of Nyamira County, Kenya - Ongubo, John Momanyi (2020)
Kenya conducts the Kenya Secondary Certificate of Education (KCSE) managed by the Kenya National Examinations Council (KNEC) and standardized for all secondary schools in the country. This study is about school improvement and academic performance of public secondary schools of Nyamira County, Kenya. The study aimed at evaluating the influence of parental involvement in education financing and student discipline as improvement variables towards academic performance in public secondary schools. The study was anchored on the KCSE performance results. Nyamira County among others has recorded low scores over the years as indicated in the KCSE results thus rendering public secondary schools’ performance in Nyamira County questionable. This study was based on the theory of performance as espoused by Elger and acknowledges the significance of descriptive research design. A total of 127 public secondary schools were sampled from the target population of 189 public secondary schools using the Krecjie and Morgan table of sample size determination. Sample respondents were 889 comprising of teachers. The researcher used a questionnaire as a primary data collection instrument. Data analysis was done using statistical package for the social sciences (SPSS) software. Based on the findings of this study, the study concluded that parental involvement is critical in the students’ academic performance among public secondary schools in Nyamira County. There exist a strong positive correlation between adequate education financing support and student’s performance in KCSE. The study also revealed that student discipline influences the academic performance of public secondary schools in Nyamira County. Disciplined pupils are likely to remain focused on their educational goals and aspirations; manage their time well, work harder in academics and show high levels of determination to succeed academically. Different lifestyle, societal norms and culture were some of the prime challenges facing the process of maintaining high discipline levels in Nyamira County. Although most secondary schools in Nyamira have got a disciplinary policy showing school rules and expected behaviour, the consequences for breaking these guidelines and the level of policy implementation in these public secondary schools in Nyamira County is wanting. From the ANOVA results, the value for F calculated is 501.176 while for F critical is 3.85. Since F calculated (501.176) is greater than F critical (3.85) and the P value is less than 0.05, this leads to the rejection of null hypotheses and adoption of the alternative hypothesis; this shows a positive significance and therefore there is need to formulate strategies that encourage parental engagement in academic improvement strategy. This is based on the revelation that lack of proper engagement procedures impeded participatory levels of parents in academic improvement strategy and therefore negatively affecting student’s academic performance. From the ANOVA test, The F calculated value is 9.956 while for F critical is 3.85. Since F calculated (9.956) is greater than F critical (3.85) and the P value is less than 0.05, this led to the rejection of null hypotheses and adoption of the alternative hypothesis revealing a positive significant relationship between levels of school financing and academic Performance of public secondary schools Nyamira County. The state policymakers should implement education reforms designed to improve resource allocation and boost student’s academic performance. The government should consider increasing the level of funding to secondary school since in some cases where social economic factors were unfavorable since it enables the affected students to academically performance preferably low. On the other hand, the ANOVA test, The F calculated value is 98.160 while for F critical is 3.85. Since F calculated (98.160) is greater than iv F critical (3.85) and the P value is less than 0.05, led to the rejection of null hypotheses and thus adoption of the alternative hypothesis. The implication is that, student discipline is a significant predictor of student academic performance at national standardized examinations among public secondary schools in Nyamira County. Hence there is need to improve on Parent’s involvement in student discipline. This will help to curb some of the challenges in instilling discipline like lack of cooperation from parents, different lifestyle and societal norms the hinder disciplinary measures. The study recommends that other stakeholders like NGOs and Faith Based Organisations should be engaged in policy development as to foster smooth implementation of all programmes towards improved academic performance in the public secondary schools within the study area. In conclusion, parental involvement, school financing and student discipline components are significant towards improvement and academic performance of public secondary schools of Nyamira County, Kenya.